Financial independence of regencies and cities in Central Java - Fafurida Fafurida; Erliz Nindi Pratiwi (Economic Journal of Emerging Markets, 2017)
This research aims to identify and to map the financial independence of the local government. This research uses ratio analysis to identify the financial independent analysis and typology to map the local government financial level. The research indicates that the financial independence tends to increase in all regions. Based on the financial independent analysis, Semarang and Tegal have lower financial dependence with the consultative relationship pattern rather than 33 other regions that have higher financial dependent level with the instructive relationship pattern. The mapping results of financial independence are in the following: ten cities or regencies have self-financial dependency below the average toward the central government, seven regencies have self-sufficient above the average toward the central government, and eighteen regencies have self-sufficient below the average toward the central government.